Il cinema bellico in Croazia negli anni '90 ; Il cinema posto-bellico in Croazia nell'ultimo decennio ; Nuove tendenze nelle cinematografie postjugoslave - Borjan, Etami (2012)
The aim of the lectures was to give a historical overview of the development of Croatian cinema in the last 20 years, after the proclamation of independence. New Croatian cinema is put in the wider context of Eastern European and other post-Yugoslav cinemas.